Content Analysis of Character Values: Theme 7 Sub-theme 2 Curriculum 2013 Textbook Revised Edition 2017 Grade V Elementary School - Syahrial S; Asrial A; Husni Sabil; Dwi Agus Kurniawan; Rahmat Perdana; Rizki Alfiana (Indonesian Journal of Primary Education, 2022)
The purpose of this study aims to identify and analyze the content of character values contained in the 2013 curriculum textbook 2013 revised edition 2017, especially on theme VII sub theme 2 class V elementary school. The research method used in this study is a qualitative research method with a type of document study. This research is a content analysis research conducted in six stages, namely unitizing, sampling, recording, reducing, inferring, and narrating. The source of data in this study is the 2013 curriculum textbook revised edition 2017 grade V elementary school. The results in this study show that in the 2013 revised edition of the 2013 curriculum textbook, class V elementary schools, especially in Theme VII sub theme 2 in each learning activity contains a content of character values that must be developed and instilled in students through a series of activities in learning and the content of character values developed in each learning tends to be different but there are still some character value content that must be developed and instilled in students the same between each learning and the development of the learner's character value content refers to eighteen character value charges but there are also some character value charges developed not based on it.